2010
DOI: 10.1007/s00382-010-0778-2
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison and analyses of the climatology of the West African Monsoon in the West African Monsoon Modeling and Evaluation project (WAMME) first model intercomparison experiment

Abstract: This paper briefly presents the West African Monsoon (WAM) Modeling and Evaluation Project (WAMME) and evaluates WAMME general circulation models' (GCM) performances in simulating variability of WAM precipitation, surface temperature, and major circulation features at seasonal and intraseasonal scales in the first WAMME experiment. The analyses indicate that models with specified sea surface temperature generally have reasonable simulations of the pattern of spatial distribution of WAM seasonal mean precipitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
108
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(114 citation statements)
references
References 58 publications
6
108
0
Order By: Relevance
“…These strong results support Druyan et al's (2009) comparison of WAMME participating RCMs, which showed HadRM3P achieved particularly high precipitation scores, although the simulated rainfall deficit over the Fouta Djallon and Cameroon highlands remains a common feature in many of these models. Thus, these results provide us with more confidence to use HadRM3P to perform the sensitivity experiments discussed in the following section.…”
Section: Precipitationsupporting
confidence: 71%
See 1 more Smart Citation
“…These strong results support Druyan et al's (2009) comparison of WAMME participating RCMs, which showed HadRM3P achieved particularly high precipitation scores, although the simulated rainfall deficit over the Fouta Djallon and Cameroon highlands remains a common feature in many of these models. Thus, these results provide us with more confidence to use HadRM3P to perform the sensitivity experiments discussed in the following section.…”
Section: Precipitationsupporting
confidence: 71%
“…The objective of the present study is to improve our understanding of the influence of initial SM and lateral boundary conditions (LBCs) on RCM simulations of the WAM climate in the framework of the West African Monsoon Modeling and Evaluation project (WAMME, Xue et al 2009). This is an international initiative in conjunction with the Coordinated Enhanced Observing Period (CEOP) and the African Monsoon Multidisciplinary Analyses project (AMMA; Redelsperger et al 2006), and investigates the role of various forcing feedbacks on the WAM dynamics using state-of-the-art GCM and RCM simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Thus land degradation affects the availability of moisture not only through the change in ET, but more importantly, through changes in circulation and moisture transport. A study using the AMMA Land Surface Model Intercomparison Project (ALMIP, Boone et al 2009) data indicated that the ratio of evaporation over precipitation in the West African monsoon area is about 52 % (Xue et al 2010). Another West African climate study with one GCM (Xue 1997) showed that evaporation change accounts for about 53 % of precipitation change after the LULC was changed.…”
Section: Mechanism Of the Responsementioning
confidence: 99%
“…The African monsoon circulation is forced by the Sahara heat low (Xue et al 2010) and the associated mid-tropospheric high. The former drives cyclonic, near surface moist southwesterly winds from the Gulf of Guinea and the high associated with this heat low in turn drives mid-tropospheric anticyclonic circulation (African Easterly Jet) that transports moisture westward out of the Sahel region into the Atlantic (Hagos and Cook 2008;Hagos and Zhang 2010).…”
Section: Mechanism Of the Responsementioning
confidence: 99%
“…Unfortunately, thus far, there have not been many such studies carried out with full scientific rigor. In a model intercomparison project, the West African Monsoon Modeling and Evaluation (WAMME, Xue et al, 2010a;Druyan et al, 2010), both GCMs and RCMs were employed for seasonal simulations. The GCM results in Fig.…”
Section: Introductionmentioning
confidence: 99%